Optimal and Sustainable Exchange Rate Regimes : A Simple Game-Theoretic Approach - Kawai, Masahiro (IMF Working Papers; Working Paper ;, 1992)
This paper examines the question of how to design an optimal and sustainable exchange rate regime in a world economy of two interdependent countries. It develops a Barro-Gordon type two-country model and compares noncooperative equilibria under different assumptions of monetary policy credibility and different exchange rate regimes. Using a two-stage game approach to the strategic choice of policy instruments, it identifies optimal (in a Pare to sense) and sustainable (self-enforcing) exchange rate regimes. The theoretical results indicate that the choice of such regimes depends fundamentally on the credibility of monetary policy commitments by the two countries' authorities. The nature of shocks to the economies and the substitutability between goods produced in the two countries also play some role. International coordination on instrument choice is necessary to design optimal and sustainable exchange rate regimes.